Of jaguars and butterflies : metalogues on issues in anthropology and philosophy - Lloyd, G. E. R. (Geoffrey Ernest Richard), 1933-; Vilaça, Aparecida, 1958- (New York : Berghahn Books, 2023)
"What are we to make of statements that jaguars see themselves as humans, or of doubts about the boundary between dreams and waking? Jointly authored by an anthropologist and a philosopher, this book investigates some of the most puzzling ideas and practices reported in modern ethnography and ancient philosophy, concerning humans, animals, persons, spirits, agency, selfhood, consciousness, nature, life, death, disease and health. The study's twin aims are first to explore the possibility of achieving a better understanding of the materials we discuss and then to see what lessons we can draw from them to challenge and revise our own fundamental assumptions"--
Are people and animals separate kinds of beings? -- Could animal-human transformations be considered as dreaming or hallucinating? -- Could we think of transformations as metaphoric? -- Similarities and contrasts with Ancient Greece -- Are there complete and incomplete transformations? -- How do things become equivalent? -- Is shamanism a kind of disease? -- Are there objects without perspectives? -- Why are some animals unable to transform? -- Do transformations need proof? -- Are shamans and healers ever doubted? -- Are transformations analogous to miracles? : Is it all about believing? -- Is proof linked to literacy? -- Could those transformations be compared to those in literary fiction? -- Should we talk about ontologies when faced with a world in flux? -- Anthropologists and philosophers.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 03, 2023).
JSTOR
Keywords: Philosophical anthropology; Anthropologie philosophique; philosophical anthropology; SOCIAL SCIENCE / Anthropology / Cultural & Social; Philosophical anthropology